Pembentukan Identitas Profesional dalam Komunitas Relawan: Perspektif Konstruksi Sosial - M Jabal Nur (Interaction: Jurnal Sosiologi Komunikasi, 2025)
This study examines the social construction of professionalism through communicative practices within the Human Initiative Volunteer Energy (HIVE) South Sulawesi volunteer community, with a focus on the Remote Area Education Program in Pattuku Village. Using a descriptive qualitative approach with participatory observation and in-depth interviews, this study reveals how the meaning of professionalism is adapted from formal definitions to contextual communicative practices. The findings reveal five dimensions of adapted professionalism: boundless dedication, accountability to beneficiaries, creative adaptability, relational ethics, and continuous learning. This adaptation occurs through three patterns of communication—horizontal, vertical, and diagonal—which function as mechanisms of socialization and legitimization. This study contributes to the understanding of organizational communication by showing how the meaning of professionalism is adapted through communicative practices in the context of volunteering.